Gestão da integração entre desenvolvimento de produtos e de tecnologias : estudo de casos em empresas industriais de médio porte e intensivas em tecnologia - Jugend, Daniel (2010)
Knowledge transfer and technological solutions to products of a company requires integration between different departments and experts involved in the process of product and technology development. Adequate transference requires the use of certain mechanisms of management by the company aiming at improving such integration. Using bibliographic review on innovation and technological management and products development process, this thesis proposes a structure that contains management practices for integration of products development (PD) and technological development (TD). In addition to that, it was carried out a qualitative research, operationalized by means of case studies in five large and medium national technology-based companies from the sector of capital goods. The findings of empirical work scrutinized technology innovation in product development within these firms, and also management practices used to integration between PD and TD. Practices adopted by companies are described and confronted with the presented theoretical approach. Recommendations, originated from the theoretical and empirics research, suggest management practices capable of guiding actions for a better development of integration between PD and TD, such as: the insertion of multitasking employees in the development team, the participation of R&D workers in activities of market research and allocation of heavyweight product manager for the conduction of products development project which demand technological innovation